Advancements in Molecular Sieves for Emerging Energy Applications - Torres, F.G.; Tapia, J.; Troncoso, O.P. (John Wiley and Sons, 2025)
The limitations of traditional energy technologies have become increasingly evident as the demand for sustainable energy solutions rises, particularly concerning efficiency and environmental impact. In this context, molecular sieves (MS) emerge as key materials to improve the properties of these energy systems due to their porous structure and high surface area. These features make them ideal for their use as electrodes or separators in batteries and capacitors, while their ability to separate molecules based on size is helpful in fuel refining for fuel cells. Common types of MS include zeolites, metal-organic framework-based materials, carbon MS, and polymers of intrinsic microporosity. In this review, the applications of MS in energy storage and conversion systems are explored examining their roles in batteries, capacitors, fuel cells, and solar cells. The mechanisms behind the performance improvement of electrodes, electrolytes, and separators are reviewed, including the mitigation of dendrite formation, the increment in catalytic activity, and the increment of cycle durability, among others. By summarizing these advancements, this work aims to show an overview of the potential of MS in the development of novel components for the fabrication of long-lasting, efficient, and ecologically friendly energy storage and generation devices.
Keywords: Energy storage; Context (archaeology); Nanotechnology; Materials science; Supercapacitor; Energy transformation; Process engineering; Engineering; Electrode; Chemistry; Electrochemistry; https://purl.org/pe-repo/ocde/ford#2.04.00